2004
DOI: 10.1159/000076954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Nitroimidazole Resistance in Metronidazole-Resistant <i>Bacteroides</i> Species Isolated from Hospital Patients in Kuwait

Abstract: Objectives: The aim of this study was to screen for infections caused by metronidazole (MTZ)-resistant Bacteroides spp., and to characterize the genes that encode the MTZ resistance. Materials and Methods: A total of 7 MTZ-resistant Bacteroides spp. were isolated from 5 patients with MTZ-resistant infections. These organisms were investigated for carriage of genes that encode MTZ resistance. The presence of these genes was investigated by PCR and the PCR products were subjected to PCR-RFLP analysis. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Soki J et al 26 , Stubbs et al 27 , Trinhs and Reysset et al 28 . Jamal W Y et al 29 had shown Metronidazole resistant Bacteroides fragilis which are in support of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Soki J et al 26 , Stubbs et al 27 , Trinhs and Reysset et al 28 . Jamal W Y et al 29 had shown Metronidazole resistant Bacteroides fragilis which are in support of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Thus maximum recovery of Bacteroides fragilis isolates were from pus (21%), and less number of isolates were from blood and aspirates. Table 4 (Chart 3) shows that out of the total 32 isolates, 14 (8%) were isolated from post-operative wound infections, 11 (6.2%) isolated from diabetic foot ulcers, 2 (1.1%) isolates were from wound infections following Burns, 2 (1.1%) were from open injury following accidents, 1 (0.5%) was isolated from decubitus ulcers, septicaemia and intra-abdominal 29 (90.7%) susceptible and 3 (9.3%) resistant for tetracycline. Thus, it was found that only one organism was resistant for metronidazole and chloramphenicol, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, because of its unstable nature on mobilizable plasmids, Nim gene-based resistance poses a real threat to the existing applications of 5-Ni drugs. Indeed, a recent study identified seven Bacteroides-resistant strains with minimum inhibitory concentrations of Ͼ32 g/ml, all containing Nim genes (23).…”
Section: Dimetridazole (Dmz) and Tinidazole (Tnz) Mtr Is Extensivelmentioning
confidence: 99%
“…Four of the nim genes are associated with mobile insertion-sequence (IS) elements, posing a threat to the existing applications of 5-Ni drugs. Indeed, one study identified seven resistant Bacteroides strains with minimum inhibitory concentrations of >32 mg ml À1 , all of which contained nim genes (Jamal et al, 2004). Even if the rate of 5-Ni resistance is still low, organisms with metronidazole resistance are beginning to emerge (Haggoud et al, 1994;Lö fmark et al, 2005).…”
Section: Introductionmentioning
confidence: 99%